2011
DOI: 10.1021/nn103077k
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Mesoporous Silica Nanoparticles with Human Red Blood Cell Membranes: Size and Surface Effects

Abstract: The interactions of mesoporous silica nanoparticles (MSNs) of different particle sizes and surface properties with human red blood cell (RBC) membranes were investigated by membrane filtration, flow cytometry, and various microscopic techniques. Small MCM-41-type MSNs (∼100 nm) were found to adsorb to the surface of RBCs without disturbing the membrane or morphology. In contrast, adsorption of large SBA-15-type MSNs (∼600 nm) to RBCs induced a strong local membrane deformation leading to spiculation of RBCs, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
440
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(477 citation statements)
references
References 64 publications
17
440
7
1
Order By: Relevance
“…In addition, the small sizes of our Odots make them have an enhanced ratio of surface area to volume, which thermodynamically increases the binding energy between Odots and the phospholipids layer. Similar explanations on the effect of particle size on membrane wrapping have been reported previously 33. Hence, the interaction of Odots with cellular membrane renders CPy‐Odots the membrane probing activity.…”
Section: Resultssupporting
confidence: 83%
“…In addition, the small sizes of our Odots make them have an enhanced ratio of surface area to volume, which thermodynamically increases the binding energy between Odots and the phospholipids layer. Similar explanations on the effect of particle size on membrane wrapping have been reported previously 33. Hence, the interaction of Odots with cellular membrane renders CPy‐Odots the membrane probing activity.…”
Section: Resultssupporting
confidence: 83%
“…Consistent with previous findings that the cytotoxicity of nanoparticles was strongly correlated to their surface charges, the toxicity disparity stemmed from different electrostatic associations between nanoparticles and cell membranes and the membrane‐compromising effects of CTAB 9, 10, 13. C‐GNRs with positive surface charges would electrostatically attach to negatively charged erythrocytes, where (1) binding of CTAB surface of GNRs with the phosphatidyl choline‐rich erythrocyte membrane and (2) bending of the erythrocyte membrane to adapt to the rigid surface of GNRs might occur 15. Lau et al found that the toxicity of C‐GNRs leading to hemolysis through the Ca 2+ pathway was largely due to the unbound CTAB residues or CTAB bilayer of C‐GNRs 12.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of the haemolysis of uncoated BFO-NP showed a weak haemolytic potential (Figure 6), comparable to that of metallic NP observed in other bio-assays. 35,36 Upon PEG coating, this potential was significantly reduced (P b 0.001, Figure 6). These statistically significant results proved that PEGylation of the metal oxide core contributed to the reduction of the interaction between cell membranes and particles surface.…”
Section: Haemolysis Assaymentioning
confidence: 99%